T1 and T2 values of human neonatal blood at 3 Tesla: Dependence on hematocrit, oxygenation, and temperature. Issue 4 (18th May 2015) - Liu, Peiying; Chalak, Lina F.; Krishnamurthy, Lisa C.; Mir, Imran; Peng, Shin‐lei; Huang, Hao; Lu, Hanzhang
Abstract : Purpose: Knowledge of blood T1 and T2 is of major importance in many applications of MRI in neonates. However, to date, there has not been a systematic study to examine neonatal blood T1/T2 relaxometry. This present study aims to investigate this topic. Methods: Using freshly collected blood samples from human umbilical cord, we performed in vitro experiments under controlled physiological conditions to measure blood T1 and T2 at 3 Tesla (T) and their dependence on several factors, including hematocrit (Hct), oxygenation (Y) and temperature. Results: The arterial T1 in neonates was 1825 ± 184 ms (Hct = 0.42 ± 0.08), longer than that of adult blood. Neonatal blood T1 was strongly dependent on Hct ( P < 0.001) and Y ( P = 0.005), and the dependence of T1 on Y was more prominent at higher Hct. The arterial T2 of neonatal blood was 191 ms at an Hct of 0.42, which was also longer than adult blood. Neonatal blood T2 was positively associated with blood oxygenation and negatively associated with hematocrit level, and can be characterized by an exchange model. Neonatal blood T1 was also positively associated with temperature ( P < 0.001). Conclusion: The values provided in this report may provide important reference and calibration information for sequence optimization and quantification of in vivo neonatal MRI studies.Magn Reson Med 75:1730–1735, 2016. © 2015 Wiley Periodicals, Inc.